First Mesozoic Thylacocephalans (Arthropoda, ?Crustacea; Cretaceous) in the Western Hemisphere: New Discoveries from the Muhi Quarry Lagerstätte. (May 2014) - Hegna, Thomas A.; Vega, Francisco J.; González-Rodríguez, Katia A.
Abstract : The first Mesozoic thylacocephalans from the western hemisphere are documented from the Muhi Quarry plattenkalk in the La Negra facies of the El Doctor Formation (Albian–Cenomanian), Zimapán Area, northwestern Hidalgo, central Mexico. They all are found in a single horizon at the base of the type section. These specimens represent two new genera and species, and a third undetermined species which likely also represents a new genus and species. Victoriacaris muhiensis is a shorted-bodied thylacocephalan with concave anterior and posterior notches as well as a beveled anterior spine. Polzia eldoctorensis is trapezoidal in outline with a rounded posteroventral corner. The third undetermined species is known only from one broken specimen, but has distinctive marginal spines that are not possessed by any other post-Cambrian thylacocephalan. The occurrence of such a diverse fauna of thylacocephalans markedly increases the diversity and geographic range of Cretaceous thylacocephalans, but does not offer any insights into the tempo of thylacocephalan extinction at the end of the Cretaceous.